Newman Error Analysis To Identify Student Errors In Solving High-Order Thinking Skills Problems Based On Self-Confidence - Nursiwi Nugraheni; Y. L. Sukestiyarno; Wardono Wardono; Masrukan Masrukan (Universitas Negeri Semarang, 2021)
This paper aims to analyze the mistakes of primary teacher education Universitas Negeri Semarang (UNNES) students in solving high order thinking skills problems with the Newman procedure. Mixed research methods were used in this study. Students are given a self-confidence questionnaire and then categorized into three levels, namely students with low, medium and high self-confidence (SC). Then by using purposive sampling, 2 students were selected in each the low group, the medium group, and the high group. The six students were given HOTS questions and then analyzed their errors according to the Newman Procedure. In results for questions C4 and C5, students with low self-confidence missed important information in the questions so that it was difficult to understand the questions and the next steps. Students with moderate self-confidence tend not to experience problems in reading and understanding the questions, but their weak points are in the process skills in C4 questions and the transformation in the C5 and C6 questions. Students with high self-confidence did not have difficulty solving C4 questions but experienced difficulties in the transformation of C5 questions and process skills in C6. This paper concludes that students with low SC are weak in terms of reading and understanding questions, students with moderate SC in terms of transformation, students with high SC are weak in terms of process skills.